(untitled) (Bangladesh Journal of Medical Biochemistry, 2018)
Tuberculosis is a common disease throughout the world, especially in developing countries. The most common form of the disease is pulmonary tuberculosis (PTB). Extra pulmonary tuberculosis (EPTB) is also a growing problem worldwide. The diagnosis of PTB and EPTB is even harder when smears and cultures are negative. Due to its nature, the diversity of clinical pictures, the diagnosis of EPTB is often difficult and late. Advances in rapid diagnostic techniques are urgently required both for the early management of the new cases of TB and for the individuals already infected with Mycobacterium tuberculosis and are at risk of developing disease. In addition to standard TB diagnostic techniques, use of new biochemical surrogate markers like LDH and gamma interferon are new suggested. This study was undertaken to evaluate the diagnostic value and accuracy of serum LDH and gamma interferon for the diagnosis of PTB and EPTB. This crosssectional study was carried out in the Department of Pathology and Microbiology, NIDCH, Dhaka and by convenient and purposive sampling, 131 patients (male 98, female 33) having age range of 20-90 years were enrolled for the study. Serum LDH and QuantiFERON-TB gold (QFT-G i.e. gamma interferon) were estimated and the result was compared with the culture and histopathology results. Performance tests were done. Prevalence was measured at 95% CI. Statistical significance was set at p<0.05. Of 131 patients 89 (67.9%) had pulmonary tuberculosis (PTB) and the rest 42 (32.1%) had extra-pulmonary tuberculosis (EPTB). Level of LDH and gamma interferon in serum of all patients was found significantly high. TB pleural effusion was detected in 64% cases. The sensitivity, specificity, positive predictive values, negative predictive values and accuracy of LDH and gamma interferon wre calculated both in PTB and EPTB. For LDH it was (SEN 89.22%, SPE 85.66%, PPV 88.82%, NPV 86.11%) and for gamma interferon (SEN 93.01%, SPE 91.64%, PPV 93.73%, NPV 91.18%) in PTB; and for LDH (SEN 89.27%, SPE 87.18%, PPV 84.35%, NPV 90.36%) and for gamma interferon (SEN 94.88%, SPE 93.65%, PPV 90.04%, NPV 95.82%) in EPTB respectively. When calculated in combination, the sensitivity and specificity was 100% and 50% respectively in both PTB and EPTB, and positive and negative predictive values of LDH and gamma interferon in combination were 94.00% and 91.58% in PTB and 90.43% and 96.71% in EPTB respectively. The study concludes that the diagnostic accuracy of LDH and gamma interferon is low when single test is done but it is significantly high when done in combination. Bangladesh J Med Biochem 2017; 10(2): 69-74